Who returns to work and why? : a six-country study on work incapacity and reintegration - Bloch, Frank S. [Herausgeber]; Prins, Rienk [Herausgeber] (Transaction Publ., 2001)
"The book examines a wide range of interventions directed at work incapacity and reintegration that are used by social security institutions, health care providers and employers. Drawing on data compiled in six longitudinal studies of day-to-day practices and experiences in Denmark, Germany, Israel, the Netherlands, Sweden, and the United States through the International Social Security Association's Project on work incapacity and reintegration (WIR project), this volume addresses two key questions: do the various interventions (by social security and health care systems) found in different countries make a difference as to work resumption patterns: and if so, what are the best interventions?" (author's abstract, IAB-Doku) ((en))
Wer kommt zurück in die Arbeit und warum : eine Sechs-Länder- Studie über Arbeitsunfähigkeit und Reintegration
Keywords: G 1.3.3.4 Wiedereingliederung; G 1.2.2 Beschäftigungs- und Arbeitsverhältnisse; G 2.3.1 Arbeitsteilung & -organisation; G 1.2.2.2 Soziale Sicherungssysteme; S 2.3 Berufsbildungspolitik; I 2.2.1 Westeuropa; I 2.3.2 Nordamerika; I 2.3.4 Asien; Berufliche Reintegration; Internationaler Vergleich; Medizinische Rehabilitation; Erfolgskontrolle; Arbeitsunfähigkeit; Menschen mit Behinderung; Soziale Sicherheit; Best practice; Quantitative Angaben; Dänemark; Schweden; USA; Israel; Niederlande; 1994-1998